2015
DOI: 10.4049/jimmunol.1500312
|View full text |Cite
|
Sign up to set email alerts
|

Mature Cystic Fibrosis Airway Neutrophils Suppress T Cell Function: Evidence for a Role of Arginase 1 but Not Programmed Death-Ligand 1

Abstract: Bacteria colonize cystic fibrosis (CF) airways, and while T cells with appropriate antigen specificity are present in draining lymph nodes, they are conspicuously absent from the lumen. To account for this absence, we hypothesized that polymorphonuclear neutrophils (PMNs), recruited massively into the CF airway lumen and actively exocytosing primary granules, also suppress T-cell function therein. Programmed Death-Ligand 1 (PD-L1), which exerts T-cell suppression at a late step, was expressed bimodally on CF a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
86
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 62 publications
(92 citation statements)
references
References 50 publications
5
86
1
Order By: Relevance
“…More recently, CF airway neutrophils, with full mature phenotype, were described to release arginase 1, activate it through proteolytic cleavage associated with primary granule exocytosis, which deprive the milieu in arginine and actively modulate T-cell function. This study supports an active inhibition of T-cell response due to neutrophil activity in CF airways (Ingersoll et al, 2015). Thus, as shown in Figure 1, the pathological events occurring in CF airways appear to trigger specific reprogramming of these cells, suggesting that neutrophils are not just passive shortlived and catabolic cells, but rather stay viable and actively contribute to airway disease (Tirouvanziam, 2006).…”
Section: New Paradigm Of Airway Neutrophilssupporting
confidence: 80%
See 1 more Smart Citation
“…More recently, CF airway neutrophils, with full mature phenotype, were described to release arginase 1, activate it through proteolytic cleavage associated with primary granule exocytosis, which deprive the milieu in arginine and actively modulate T-cell function. This study supports an active inhibition of T-cell response due to neutrophil activity in CF airways (Ingersoll et al, 2015). Thus, as shown in Figure 1, the pathological events occurring in CF airways appear to trigger specific reprogramming of these cells, suggesting that neutrophils are not just passive shortlived and catabolic cells, but rather stay viable and actively contribute to airway disease (Tirouvanziam, 2006).…”
Section: New Paradigm Of Airway Neutrophilssupporting
confidence: 80%
“…New neutrophil phenotypes, such as T-cell suppressive granulocytic myeloid-derived-suppressor cells (MDSCs) (Rieber et al, 2013;Ingersoll et al, 2015) broaden the repertoire of neutrophil versatility in CF and underscore their importance beyond direct pathogen killing. While the surrounding pro-inflammatory CF microenvironment substantially affects neutrophil phenotype and function, the intrinsic CFTR defect also seems to modulate neutrophil homeostasis and granule release (Pohl et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Surprisingly a prominent finding revealed by our transcriptomic analysis of both infected mice and humans was the prominent up-regulation in both blood and tissue of Arginase-1, which led us to investigate and confirm its presence at the protein level within the lesions of infected mice. Arginase-1 is known to antagonise the iNOS microbicidal pathway and to inhibit T cell immunity in other infections (27) (28) (29) (30) and thus may be a contributing factor to why in B. pseudomallei infection sterilising immunity is rarely achieved.…”
Section: Discussionmentioning
confidence: 99%
“…Further studies revealed a role for airway neutrophils in regulation of the adaptive immune system, further emphasizing the multidimensional importance of neutrophil plasticity [37]. For example, a strong immunosuppressive function was identified in CF airway neutrophils, which can downregulate T-cell activity through the release and activation of arginase I, concomitant with granule exocytosis [49]. Activated neutrophils may also impact T cells positively within CF airways but also within the lymphatic compartment by displaying antigen-presenting cell capabilities (e.g., expression of CD80, CD86, and MHC II).…”
Section: Neutrophilsmentioning
confidence: 99%